BELAJAR ATAU BERMAIN: UPAYA MEMAHAMI PERKEMBANGAN ANAK USIA DINI DALAM PEMBELAJARAN DI LEMBAGA PAUD - Nurhasanah, Nurhasanah (Institut Agama Islam Negeri Bone, 2019)
The high requirement of primary educational institutions for high quality educational inputs is responded well by the educational institutions below them, namely early childhood educational institutions. Especially the need of reading, counting, writing and others is a top priority for elementary schools in accepting graduates from early childhood educational institutions. Although getting a very good in response, but it does not necessarily facilitate the realization of this. On one side of early childhood development includes aspects of playing, or learning while playing will be eroded by the need to fulfil the demand for further educational institutions. This paper is intended to explore and explain aspects of early childhood development, choose when they should play and when they should learn, with the aimed that educators do not sacrifice the grow periods of early childhood that they should go through but are lost because of efforts to meet the demand for further educational institutions need. The research method in this paper uses the literature review approach.Â Keywords: early childhood development, playing, and learning